2017
DOI: 10.3390/w9110884
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Water Exchanges between China’s Poyang Lake and Its Saucer-Shaped Depressions on River Deltas

Abstract: Abstract:The saucer-shaped depressions located at the river deltas of Poyang Lake are typical floodplain shallow sub-lakes subject to river-lake connection or isolation. The hydrological connectivity between these depressions and the main lake has a major influence on the hydrologic function and ecological integrity of the lake-floodplain and associated wetland habitats. This study explored the water level fluctuations and water exchange processes between the Poyang Lake and three typical saucer-shaped depress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 32 publications
1
1
0
Order By: Relevance
“…During periods of low water, seasonal lakes recharge the river or the main lake through groundwater because of its lower water level. These results were observed in the field (Cullmann et al, 2006;Wu & Liu, 2017).…”
Section: Groundwater Flow Fieldsupporting
confidence: 67%
“…During periods of low water, seasonal lakes recharge the river or the main lake through groundwater because of its lower water level. These results were observed in the field (Cullmann et al, 2006;Wu & Liu, 2017).…”
Section: Groundwater Flow Fieldsupporting
confidence: 67%
“…In the months when Landsat data were unavailable, we considered the downscaling method proposed by Wu et al [11]. based on NDWI to obtain a higher resolution from low-resolution data.…”
Section: Water Surface Extraction Methods In Unavailable Months For L...mentioning
confidence: 99%
“…Taking the sub-shaped lakes (Bang Lake and Sha Lake) of Poyang Lake as the research object, Li et al [10] conducted a comprehensive analysis of the transformation relationship and exchange flux of groundwater in the sub-lakes using hydrological, thermodynamic, and hydrodynamic methods. Wu et al [11] used water level observation data to explore the water level change and hydrological exchange process at Poyang Lake and three typical saucer lakes; the study showed that the main lake and the saucer lake show strong seasonal and spatial correlations between water level changes and hydrological exchange processes. Liu et al [12], based on long-term remote sensing images, analyzed the spatio-temporal variation characteristics of seasonal lakes and their influencing factors and ecological effects.…”
Section: Introductionmentioning
confidence: 99%
“…Hu et al, 2015). All of these shallow depressions have a saucer-shaped profile, and the maximum water depth is usually less than 2 m (Wu & Liu, 2017). They play an important role in flood mitigation storage and biodiversity protection (Z.…”
mentioning
confidence: 99%